The existence of legal anthropology in the present - Andi Dewi; Arfani Ichsan; Muh Fadlan Fadilc (Indonesia Prime, 2021)
The era of pluralism shows the development / existence of legal anthropology in the present day. One example of such development is the Indonesian state which has a diversity of laws, namely national laws and customary laws that affect each other. Although sometimes there is a clash of state laws (national laws) with the other laws (local customary law) will be attempted to resolve the problem. But it is also worth noting the differences from legal anthropology and customary law ranging from objects, approaches, nature of research, and norms. In addition, legal pluralism cannot be separated from the plurality of society so that in the determination of national laws, of course, it should not also be separated from the law from society (the concept of legal unification) so that there is a coordinated, more orderly implementation of the law and its performance is expected to increase. In the development of legal anthropology today was initially influenced by the thoughts of Bohannan, Gluckman, and Gulliver directed to the mechanisms and agencies of dispute resolution based on the laws of the colonial government and the governments of independent countries. Then entering the phase of legal pluralism influenced by the views of Sally F. Moore, Snyder, and F. von Benda-Beckmann directed to the studies of legal pluralism beyond dispute resolution. The study of legal pluralism with holistic methods with a focus on the process of law-making, legal norms / laws and regulations, the implementation of law, and law enforcement makes this anthropology very interesting to learn further. In addition, in this legal anthropology also has aspects to dispute resolution both litigation and non-litigation which is certainly very useful to be studied and studied by law enforcement, because generally the law nationally is not formed without any influence from a community perspective